Mercury contamination in the Red river watershed: a review of the contaminated sites - Ha, Dang Thi; Coynel, Alexandra; Deschatre, Marine (Vietnam Journal of Earth Sciences, 2014)
This study is based on two sampling campaigns covering the whole Vietnamese Red River watershed in 40 sites at low and high water levels during 2009 in order to determine the seasonal and spatial variations of Hg concentrations in stream sediments. The results showed that the Hg concentrations during low water level were clearly higher than that during high water level, demonstrating an effect of particle (grain) size (i.e. significant contribution of less mercury-contaminated particles in high water level). In addition, in order to assess spatial distribution of the Hg contamination in the Red River watershed and localize geochemical anomalies, multidimensional statistical analyses combined with Hg maps generated by GIS tool were used. We observed that the high mercury anomalies are originated from the important pollutant sources (mining/smelting) located in the upstream and mid- Red River watershed, demonstrating an impact of anthropogenic activities on river Hg concentrations. Finally, the comparison between the Hg concentrations in the stream sediment from the Red River watershed and the consensus-based freshwater sediment quality guidelines (SQGs) indicated that the sediment quality for important areas of the Red River watershed is rather poor and probably represents serious threats to aquatic life. References Adrienne, R.F., Peter, V.H., Brian, C.H., 2008: Spatial and seasonal patterns of mercury concentrations in fish from the St. Lawrence River at Cornwall, Ontario: Implications for monitoring. Journal of Great Lakes Research 34, 72-85. Balogh, S., Meyer M., Kentjohnson, D., 1998: Transport of mercury in three contrasting river basins. Environ. Sci. Technol.32, 456-462. Berg, M., Stengel, C., Phạm, T.K.T., Pham, H.V., Sampton, M.L., Leng, M., 2007: Magnitude of arsenic pollution in the Mékong and Red River Deltas-Cambodia and Vietnam, Science of the Total Environment 327, 413-425. Brigham, M., Wentz, D., Aiken, G., Krabbenhoft, A., 2009: Mercury cycling in stream ecosystems.1. Water column chemistry and transport. Environ. Sci. Technol. 43, 2720-2725. Coynel, A., Blanc, G., Marache, A., Schäfer, J., Dabrin, A., Maneux, E., Bossy, C., Masson, M., Lavaux, J., 2009: Assessment of metal contamination in a small mining- and smelting-affected watershed: high resolution monitoring coupled with spatial analysis by GIS, J Environ Monit.11, 962-976. Dang, T.H., Coynel, A., Grosbois, C., Blanc, G., Orange, D., Etcheber, H., Le, L.A., 2011: Distribution, source and flux of arsenic in a typical humid tropics river originating from the Himalaya Mountains: the Red River watershed (China/Vietnam). Proceeding of 23eme RST conference, Bordeaux, France. Dang, T.H., Coynel, A., Orange, D., Blanc, G., Etcheber, H., Le, L.A., 2010: Long-term monitoring (1960-2008) of the river-sediment transport in the Red River Watershed (Vietnam): temporal variability and dam-reservoir impact. Science of the Total Environment 408, 4654-4664. Guangle, Q., Xinbin, F., Shaofeng, W., Tangfu, X., 2006: Mercury contaminations from historic mining to water, soil and vegetation in Lanmuchang, Guizhou, southwestern China. Science of the Total Environment 368, 56-68. Ho, T.L.T., Cao, T.S., Tran, T.L., Kurosawa, K., Egashira, K., 2010: Assessment of surface and groundwater quality in pig-raising villages of Hai Duong province in Vietnam. Journal of the Faculty of Agriculture, Kyushu University 55, 123-130. Le, T.P.Q., Garnier, J., Gilles, B., Sylvain, T., Chau, V.M., 2007: The changing flow regime and sediment load of the Red River, Viet Nam. Journal of Hydrology 334, 199-214. MacDonald, D.D., Ingersoll, C.G., Berger, T. A., 2000: Development and Evaluation of Consensus-Based Sediment Quality Guidelines for Freshwater Ecosystems. Arch. Environ. Contam.Toxicol.39, 20-31. MacFarlane, M., 2004: Mercury concentrations in water and sediment in Resurrection Creek, Alaska.Final Report, 27p. Maria, H.D.P., Milton, L.L.F., Elba, C.T., 1997: Heavy metals in stream sediments from copper and gold mining areas in southern Brazil. Journal of Geochemical Exploration 58, 133-143. Mlayah, A., Ferreira da Silva, E., Rocha, F., Ben Hamza, Ch., Charef, A., Noronha, F., 2009: The OuedMellègue: Mining activity, stream sediments and dispersion of base metals in natural environments, North-western Tunisia. Journal of Geochemical Exploration 102, 27-36. Nguyen, M.P., Kang, Y., Sakurai, K., Iwasaki, K., Chu, N.K., Nguyen, V.N., Le, T.S., 2010: Levels and Chemical Forms of Heavy Metals in Soils from Red River Delta, Vietnam. Water, Air, and Soil Pollution 207, 319-332. Schäfer, J., Blanc, G., Audry, S., Cossa, D., Bossy, C., 2006: Mercury in the Lot-Garonne River system (France): Sources, ﬂuxes and anthropogenic component. Applied Geochemistry 21, 515-527. Spadini, L., Charlet, L., 2003: Distribution of anthropogenic mercury in French Guyana river sediments downstream from gold mining sites. Journal of Physical IV France 107, 1263-1266. Subramanian, V., Madhavan, N., Rajinder, S., Lundin, L.C., 2003: Nature of distribution of mercury in the sediments of the River Yamuna (tributary of the Ganges), India. J. Environ. Monit.5, 427-. Viers, J., Dupréa, B., Gaillardet, J., 2008: Chemical composition of suspended sediments in World Rivers: New insights from a new database. doi:10.1016/j.scitotenv.2008.09.053.